ON THE ELZAKI SUBSTITUTION AND HOMOTOPY PERTUBATION METHODS FOR SOLVING PARTIAL DIFFERENTIAL EQUATION INVOLVING MIXED PARTIAL DERIVATIVES - Babajide, Ayeni O.; Oluwatobi, Idowu K (FUDMA JOURNAL OF SCIENCES, 2021)
This paper investigated new methods of solving partial differential equations involving mixed partial derivatives that were initially solved by Sujit and Karande in their usual notation by making use of Laplace substitution method. The methods investigated in this paper are Elzaki Substitution and Homotopy perturbation Methods of solving partial differential equations with mixed partial derivatives. Finally, the results obtained showed that Elzaki Substitution method and Homotopy Perturbation method are accurate and efficient method to solve partial differential equations involving mixed partial derivatives